Diabetic and Elder Patients Experience Superior Cardiovascular Benefits After Gastric Bypass Induced Weight Loss - Pereira, Pedro R.; Guimarães, Marta; Morais, Tiago; Pereira, Sofia S.; Nora, Mário; Monteiro, Mariana P. (Frontiers in Endocrinology, 2018)
BACKGROUND/OBJETIVES: Obesity and obesity related co-morbidities are well recognized risks for cardiovascular (CV) disease and mortality. Weight loss improves CV risk factors and the efficacy of bariatric surgery in decreasing CV mortality is now well established. Our aim was to assess CV risk progression and occurrence of CV events in a cohort of patients that underwent Roux-en-Y gastric bypass (RYGB) for obesity treatment in a single academic public center. SUBJECTS AND METHODS: 10-year CV risk was estimated using the Framingham Equation at baseline and 2 years after RYGB surgery in our patients cohort (n=260). In the subgroup with a follow-up time longer than 4 years after surgery (n=185; mean 5.4±0.1 years), CV risk adjusted for the time length after RYGB was similarly estimated and the occurrence of CV events for outcome adjudication was monitored during the same time period by reviewing the hospital patients’ record, the electronic national health system patient register and our center outpatient clinic records. RESULTS: 10-year CV risk was significantly reduced 2 years after surgery when compared to baseline, with reductions of 1.65±0.25% in the risk of CV disease. Patients with prior type 2 diabetes and aged 50 years or older experienced a significantly superior CV risk reduction, with diabetic patients experiencing a reduction of their 10-year CV disease risk of 3.58±1.11% versus a reduction of1.31±0.20% in non-diabetic patients and with the 10-year risk of CV disease dropping 3.41±0.75% in patients older than 50 versus a reduction of 0.99±0.18 in patients up to 50 years. For the subgroup of patients with a longer follow-up time, baseline CV risk estimation predicted the occurrence of 6.08±0.56 cardiovascular disease (CVD) events, 3.87±0.39 coronary heart disease (CHD) events, 1.49±0.22 myocardial infarctions (MI), 0.71±0.09 strokes, 0. 28±0.05 deaths from CHD and 0.35±0.05 deaths from CVD. No CV events were adjudicated in this subgroup during follow-up. CONCLUSIONS: RYGB significantly improves CV risk and prevents the occurrence of CV events. For similar weight loss, diabetic and elder patients experience a superior CV risk improvement and may have additional CV benefits after bariatric surgery.